Psychological mechanisms of healthy lifestyle and academic burnout: a moderated mediation model - Lu, Jiantao; Wang, Yu; Liu, Xinjing; Zhang, Qian; Yan, Yuqin (Frontiers in Psychology, 2025)
ObjectiveAcademic burnout is a prevalent phenomenon among college students. According to the Conservation of Resources Theory, when there is an imbalance between invested resources and expected returns, individuals may suffer from academic or job burnout. If an individual has sufficient resources, these resources may relieve the negative problem. Healthy lifestyle is believed to improve brain health and provide resources. However, limited research has examined the psychological mechanisms that link academic burnout and a multidimensional healthy lifestyle.MethodsA sample of 1,186 undergraduate students from freshmen to seniors were recruited using the stratified cluster random sampling method. The participants completed online questionnaires that assessed the healthiness of their lifestyle, dormitory conflict coping style, and academic burnout in April 2021. Bivariate correlation and a moderated mediation model were constructed to examine the relationships among these variables.ResultsThe results indicated that (1) healthy lifestyle was negatively correlated with academic burnout (r = −0.496, p < 0.001), coping styles of competition (r = −0.281, p < 0.001) and avoidance (r = −0.210, p < 0.001), but positively correlated with coping styles of cooperation (r = 0.342, p < 0.001) and obedience (r = 0.134, p < 0.001); (2) academic burnout was positively correlated with coping styles of competition (r = 0.331, p < 0.001) and avoidance (r = 0.305, p < 0.001) and negatively correlated with coping styles of cooperation (r = −0.227, p < 0.001); and (3) the direct path of healthy lifestyle on academic burnout was partially mediated by coping styles of competition (effect = −0.04, 95%CI: [−0.05,-0.03]) and avoidance (effect = −0.03, 95%CI: [−0.04,-0.02]), which was moderated by gender (β = −0.48, p = 0.007).ConclusionThe findings offer valuable insights into the psychological mechanisms underlying the association between academic burnout and multidimensional healthy lifestyle among general college students, as indicated that college students with healthier lifestyles tend to use fewer coping styles of competition and avoidance, leading to a lower level of academic burnout. Such effect is more pronounced among female college students. This study provides a new perspective for the prevention and intervention in college students’ academic burnout.